2018
DOI: 10.3390/ijms19124033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant Material and Surface on Differentiation and Proliferation of Human Adipose-Derived Stromal Cells

Abstract: For the guided regeneration of periimplant hard and soft tissues, human adipose-derived stromal cells (hADSC) seem to be a promising source for mesenchymal stromal cells. For this, the proliferation and differentiation of hADSC were evaluated on titanium and zirconia dental implants with different surface treatments. Results were compared to edaphic cells as human osteoblasts (hOB) and human gingival fibroblasts (HGF). Primary cells were cultured on (1) titanium implants with a polished surface (Ti-PT), (2) sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…It seems that the expression of FAK is upregulated during osteo-specific differentiations, and it regulates the synthesis of osteo-specific proteins [24,26]. This correlates with hints for a beginning osteogenic differentiation of hADSC cells and an increased expression of osteo-specific proteins [8].…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…It seems that the expression of FAK is upregulated during osteo-specific differentiations, and it regulates the synthesis of osteo-specific proteins [24,26]. This correlates with hints for a beginning osteogenic differentiation of hADSC cells and an increased expression of osteo-specific proteins [8].…”
Section: Discussionmentioning
confidence: 72%
“…The behaviour of hADSCs, a promising cell source for guided oral tissue regeneration, and edaphic cells, as hOB and HGF, on titanium and zirconium dioxide with smooth and rough surface textures were systematically analysed. Previously, we demonstrated that the cell viability and proliferation rate were neither disturbed by titanium nor zirconium dioxide [8]. Observed cytotoxic effects were insignificant.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations